Hollywood portraits and influence the latin America culture (2016)
This research studies the influence that the cinema has over the Latin stereotypes. Over the years Hollywood has created a global phenomenon around the world as they have the control about the Cinematographic Industry, for this reason they are a communication bridge between cultures. In a sense, they have created stereotypes of people and in this way they created an image of people from different countries and cultures, but sometimes those images could be negatives and sometimes those are positives depending on how much Hollywood knows about the culture they are referring. It is highly probable that Latin American people have been adapted to the different behaviors that they perceive from the North American people and is this way they change their way to think. Also, this research focuses on the importance of being aware of the stereotypes that Hollywood are showing all the time with profitable purposes.